Algoritma Ekstraksi Informasi Berbasis Aturan - Agny Ismaya (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
The information in in the audit report of local government financial statement (LHP LKPD) was not managed digitally. The information in LHP from 33 provinces has just accumulate in a place without next process to take its main information. The absence of information searching application inhibit the learning process of the existing reports in advance. Therefore, an application can extract information from a set of LHP documents are needed to get main information, called criteria, consequence, cause, response, and audit advice. This research creates a tool to extract the information in the audit report of local government financial statement (LHP LKPD). Information extraction method that used in this research is rule-based classification and pre-processing method that used is POS Tagging. The objective of information extraction in this research finds some sections in audit finding (Temuan Pemeriksaan-TP) that are criteria, consequence, cause, response, and audit advice. The accuracy of training and test data are 98,27% and 89,77%. Decrease accuracy caused by usage of pdf2text that do not give a convertible identical between the input and output data, and usage of wordmatch method for classification.